Improved GIS Techniques and a Novel Physico-Chemical Risk Index for Surface Water Quality Assessment: A Case Study of the Al-Garraf Oil Field - Nurul Shahzira Hazri,; Sahriah Basri,; Azran Mohd Zainoodin,; Siti Kartom Kamarudin, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Petroleum hydrocarbons and waste streams have polluted the environment, harmed human health, affected socioeconomic conditions, and impacted communities in oil-producing countries. The aim of the study is to identify hotspots of contaminated water, create spatial risk maps of pollution from the petroleum industry and develop a novel index to estimate ecosystem pollution named physico-chemical risk index (PRI). Ten sites in the Al-Gharraf oil fi eld were analyzed for their water quality. The highest results of the six-month sample analysis were PH (8.7), DO (11.5 mg/L), turbidity (70.3 NTU), temperature (34 C), BOD5 (37.8 mg/L), COD (101 mg/L) and TSS (109 mg/L). To achieve the above objectives, different methods and techniques were used; one of them is inverse distance weighting (IDW) with GIS to create geographical maps of the measured parameters. The IDW method was used to accurately map the distribution of ecosystem parameters of the oil fi eld. The PRI was performed to compare the threshold values for pollutant elements with the contamination of the site. The threshold value for contaminated water in Garraf oil field is 24.328 and is determined by the PRI index. The analysis is carried out at regular intervals and compared with the threshold values. This work has created an important database for the oil industry that should be used to monitor ecosystems.